Optical coherence tomography angiography in eyes with retinal vein occlusion - Tsai, Grace; Banaee, Touka; Conti, Felipe; Singh, Rishi (Journal of ophthalmic & vision research, 2018)
Optical coherence angiography (OCTA) is a noninvasive technique that has been introduced in recent years to detect ophthalmological pathology. The growing usage of OCTA to detect retinal abnormalities can be attributed to its advantages over the reference-standard fluorescein angiography (FA), although both of these techniques can be used in association. OCTA's advantages include its dye independency, its ability to produce depth-resolved images of retinal and choroidal vessels that yield images of different vascular layers of the retina, and the better delineation of the foveal avascular zone. OCTA's disadvantages include the lack of normalized patient data, artefactual projection issues, and its inability to detect low-flow lesions or pathologic conditions. Different OCTA platforms use unique algorithms to detect microvasculature, which are implemented in both spectral-domain (SD) and swept-source (SS) OCT machines. Microvascular changes in retinal vein occlusions (RVOs) are visible in both the superficial and deep capillary networks of the retina in OCTA. These visualizations include a decrease in foveal and parafoveal vascular densities, non-perfusion areas, capillary engorgement and telangiectasias, vascular tortuosity, microaneurysms, disruption of the foveal perivascular plexus, and formation of collateral vessels. The restricted field of view and inability to show leakage are important limitations associated with the use of OCTA in RVO cases. In this article, we present a brief overview of OCTA and a review of the changes detectable in different slabs by OCTA in RVO cases published in PubMed and Embase.